2015
DOI: 10.1002/polb.23804
|View full text |Cite
|
Sign up to set email alerts
|

Transient bioelectronics: Electronic properties of silver microparticle-based circuits on polymeric substrates subjected to mechanical load

Abstract: Transient soft bioelectronics are capable of forming conformal contacts with curvilinear surfaces of biological host tissues and organs. Such systems are often subject to continuous static and dynamic loads from the biological host. In this article, we present investigation of electronic attributes of transient soft bioelectronic circuits subjected to mechanical force and influence of substrate's transiency on the transiency of the whole device; also, characterize and quantify loss of functionality in triggere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Lithium‐ion battery technology is a well‐established, mature, and commercialized technology; here, we are integrating a variation of this technology with our new approach toward transient electronics, which is ultimately based on a hybrid approach of physical redispersion of insoluble materials, and chemical dissolution of soluble ones. In our previous studies, we have reported electrical and mechanical properties of such hybrid systems. The transient primary Li‐ion batteries we report here incorporate this technology and are consist of electrodes comprise of active materials similar to those in conventional Li‐ion batteries while swelling force of the substrate/casing materials is utilized to introduce transiency through fragmentation and redispersion of the active materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium‐ion battery technology is a well‐established, mature, and commercialized technology; here, we are integrating a variation of this technology with our new approach toward transient electronics, which is ultimately based on a hybrid approach of physical redispersion of insoluble materials, and chemical dissolution of soluble ones. In our previous studies, we have reported electrical and mechanical properties of such hybrid systems. The transient primary Li‐ion batteries we report here incorporate this technology and are consist of electrodes comprise of active materials similar to those in conventional Li‐ion batteries while swelling force of the substrate/casing materials is utilized to introduce transiency through fragmentation and redispersion of the active materials.…”
Section: Introductionmentioning
confidence: 99%
“…Jimbo et al reported swallowable batteries based on Zn and Pt electrodes and ceramic porous separator; maximum potential of 0.42 V and current of 2.41 mA were achieved. 9 More recently, Kim et al reported edible water activated sodium batteries based on melanin electrodes where a potential of 0.6-1.06 V and current of [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] lA, depending on design, was achieved. 10,11 An intrinsically transient battery capable of environmental resorption was first reported by Yin et al where Mg anode and biodegradable metals (Fe, W, or Mo) cathodes were used with a transient polymer casing; potentials ranging from 0.45 to 0.75 V (depending on cathode materials) were reported.…”
mentioning
confidence: 99%
“…Transient electronics is an emerging technology with paramount potentials in a wide range of applications such as biomedical devices [1][2][3], environmental sensors, and hardware security [4,5]. Examples of transient electronic devices include transistors [1], mechanical energy harvesters [6], energy storage devices [7,8] and functional circuits for radio frequency (RF) transmission [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The new class of devices are designed to dissolve/disintegrate in a fast and controlled manner, after they serve their purpose . Recently, researchers have studied a variety of transient components including substrates, electronic components, system level devices, and batteries …”
Section: Introductionmentioning
confidence: 99%